Pengaruh Arus Kas Dan Laba Bersih Terhadap Harga Saham Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2018 – 2022 - Arseto, Dedy Dwi; Winda, Winda; Herdiansyah, Endra (Accounting Progress, 2024)
This research aims to determine the effect of cash flow and net profit on share prices in mining companies listed on the Indonesian Stock Exchange for the period 2018 - 2022. The research method used is a quantitative method using SPSS version 25.00. The analytical method used in this research is using instrument tests, namely validity and reliability tests. Classic assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis tests, namely T test and F test. The results of SPSS in this research are that the Cash Flow variable has an effect on Stock Prices, variables Net Profit influences Share Prices, then Cash Flow and Net Profit simultaneously influence Share Prices.